Prevalence and temporal trend of prematurity in Brazil before and during the COVID-19 pandemic: a historical time series analysis, 2011-2021 - Marcos Alberton; Vanessa Martins Rosa; Betine Pinto Moehlecke Iser (Ministério da Saúde do Brasil, 2023)
Abstract Objective: to measure the prevalence of prematurity according to the Brazilian macro-regions and maternal characteristics over the past 11 years; to compare the proportions during the COVID-19 pandemic (2020-2021) with those of the historical series (2011-2019). Methods: this was an ecological study, with data from the Live Birth Information System; the prevalence was calculated according to year, macro-region and maternal characteristics; time series analysis was performed using Prais-Winsten regression model. Results: the prevalence of preterm birth in 2011-2021 was 11.1%, stable; the average in the pandemic period 11.3% (95%CI 11.2;11.4%) was similar to that of the base period 11.0% (95%CI 10.6;11.5%); the North region (11.6%) showed the highest proportion between 2011 and 2021; twin pregnancy (56.3%) and pregnant women who had 4-6 prenatal care visits (16.7%) showed an increasing trend (p-value < 0.001); the highest prevalence was observed for extremes of maternal age, pregnant women of Black race/skin color, indigenous women and those with lower level of education. Conclusion: preterm birth rates were highest for socially vulnerable pregnant women, twin pregnancies and in the North; stable prevalence, with no difference between periods.